Functionality of Preface in the Integral Perception of Text (“Trans-Atlantic” by Witold Gombrowicz) - Alyona Tychinina (Pitannâ Lìteraturoznavstva)
The methodology of detection of paratextual connections detailed by Gerard Genette is analyzed. It is proved that such at first sight peripheral elements of a text are able not only to frame it specifically but also to make possible its transformation into a book. It is emphasized that paratextual modi respectively generate the mechanism of receptive action, narrow or/and broaden the expectation horizon of a reader. Subsequently, adjusted by the experience, they form a different perspective of perception which nevertheless is restricted and emphasized by a kind of paratextual “frame” that is sometimes called the interpretational one.